(untitled) (Kajian Bisnis Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2025)
The issue of accuracy in completing work by employees often receives less attention, even though the Company has improved its work services so as to achieve user and employee satisfaction. This study focuses on the impact of export service quality, and punctuality on employee Job Performance of X Freight Forwarding Company. This research approach used a Quantitative method. Flowcharts was used to illustrate the export service process carried out by freight forwarding employees. Quantitative methods were used to test hypotheses using Smart PLS 4.1.1.2 software. The selection of sample criteria was based on purposive sampling, with an equal number of employees, namely 23 men and 23 women in the export service department. Meanwhile, primary data was collected from 46 employees through accidental sampling using a 1-5 Likert scale questionnaire. The observation found that the export service work of freight forwarding X involves coordination between the exporter, freight forwarding, and shipping. The process starts from booking ship space and submitting documents such as Shipping Instructions to issuing Delivery Order and completing export documents such as Notice of Export of Goods (PEB), and Master Bill of Lading (MBL), which has the potential to cause Job Performance or dissatisfaction. Freight forwarding functions as an intermediary. The findings of the quantitative analysis show that timeliness in completing work has a positive and significant effect on Job Performance, while the Job Quality of freight forwarding employees does not affect Job Performance. Path coefficients Moderated Mediation Analysis (MGA) results found statistically significant differences in the effect of Timeliness on Job Performance between Male and Female groups.